2008
DOI: 10.1590/s0074-02762008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of toll-like receptor 2 and 4 genes in Chagas disease

Abstract: Chagas' disease (CD) is caused by infection with the intracellular protozoan parasite, Trypanosoma cruzi, and is the major cause of cardiomyopathy and heart failure in endemic regions of Colombia and South America (Guhl 1999, WHO 2002. A wide clinical spectrum is observed in the chronic phase of CD, varying from a relatively benign indeterminate form to gastrointestinal compromise or chronic cardiomyopathy that is usually fatal. The fact that only 20-30% of the infected individuals develop cardiomyopathy sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
7
11
0
1
Order By: Relevance
“…In previous studies, this was not observed, 8 but our findings accord with the reported lack of effect on infection per se. 23 Our results also support the finding that common TLR1 and TLR2 SNPs do not seem to influence CD or CCC 8 and show the respective lack of impact for a frequent TLR6 variant. The reason for the lack of impact remains unclear but may involve redundancy of TLR signaling.…”
supporting
confidence: 88%
“…In previous studies, this was not observed, 8 but our findings accord with the reported lack of effect on infection per se. 23 Our results also support the finding that common TLR1 and TLR2 SNPs do not seem to influence CD or CCC 8 and show the respective lack of impact for a frequent TLR6 variant. The reason for the lack of impact remains unclear but may involve redundancy of TLR signaling.…”
supporting
confidence: 88%
“…In our study, the 2258A allele was present only in Europeans and not in other populations. These data are supported by data from previous studies showing that this SNP is not present in Asian populations, such as those from Taiwan (12), South Korea (45,62), and India (7); in a Chinese Han population (32); in one African cohort from Ethiopia (8); and in one American cohort from Colombia (63). In a southeastern Chinese population, the TLR2 2258A allele was found at a very low frequency and was not associated with susceptibility to tuberculosis (60).…”
Section: Discussionsupporting
confidence: 86%
“…This is in concordance with previous studies on other parasitic infections. In a previous study, frequencies of TLR4 Asp299Gly and Thr399Ile polymorphism did not show any significant differences in the distribution of alleles or genotypes between patients with chagasic cardiomyopathy and asymptomatic subjects [17]. In another study, TLR2 196-174 del heterozygosity was associated with protection from cerebral malaria (OR 0.34, 95% confidence intervals 0.16, 0.73) [18].…”
Section: Discussionmentioning
confidence: 92%